Risk Management Implementation in Enhancing Bank Performance Stability - Ida Ayu Nuh Kartini; R.Frengkly Listiya Dendi Wicaksana; Muhamad Rafli Fatahila (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the implementation of integrated risk management in enhancing the performance stability of conventional commercial banks in Indonesia during the 2019–2023 period. A quantitative approach was employed using panel data regression analysis based on 125 firm-year observations from 25 commercial banks listed on the Indonesia Stock Exchange (IDX). The study evaluates the effects of credit risk, market risk, and operational risk management on banking performance, measured by Return on Assets (ROA), Capital Adequacy Ratio (CAR), and Non-Performing Loans (NPL). The findings reveal that integrated risk management significantly improves banking performance stability. Credit risk management exhibits the strongest positive influence on ROA (β = 0.412; p < 0.01) and CAR (β = 0.367; p < 0.01), while significantly reducing NPL (β = −0.289; p < 0.01). Market risk and operational risk management also demonstrate significant relationships with all performance indicators, although with relatively smaller coefficients. These findings suggest that comprehensive enterprise risk management enhances financial resilience, strengthens institutional stability, and supports sustainable banking performance amid economic uncertainty. The study contributes empirical evidence supporting integrated risk governance as a strategic driver of long-term banking sustainability in emerging economies.